Does the timing of mock embryo transfer trial improve implantation in intracytoplasmic sperm injection cycles? - YOLDEMİR, AHMET TEVFİK (TAYLOR & FRANCIS LTD, 2011)
Aim. To determine if endometrial trauma during embryo transfer trials (ETTs) improves implantation and clinical pregnancy rates in intracytoplasmic sperm injection treatment cycles. Patients. One-hundred fifty women undergoing their first IVF treatment were included in a prospective randomised study in a University hospital clinic. ETTs were performed either on day 21 of the previous cycle, or on day 6 of the controlled ovarian hyperstimulatin (COH) cycle, or conducted at least two cycles before COH cycle. Clinical pregnancy and implantation rates were compared between the groups. Results. There was no difference between the groups in terms of clinical pregnancy or implantation rates. Conclusion. Endometrial trauma by ETTs performed either during the preceeding cycle or on day 6 of the COH cycle does not improve pregnancy rates.
Keywords: Mock transfer; trial transfer; endometrial trauma; implantation; IN-VITRO FERTILIZATION; CONTROLLED OVARIAN HYPERSTIMULATION; GONADOTROPIN-STIMULATED CYCLES; PERIIMPLANTATION ENDOMETRIUM; HISTOLOGICAL-EVALUATION; INVITRO FERTILIZATION; OVULATION INDUCTION; UTERINE RECEPTIVITY; OOCYTE RETRIEVAL; LOCAL INJURY